Branded content in the sound medium: comparative study of its suitability in radio versus podcasting - Fitó-Carreras, María (2024)
Branded content creation is seeing a surge in response to the gradual loss of effectiveness of conventional advertising. This paper analyzes the degree of suitability of the radio medium for the development of the branded content technique, in contrast to podcasting, from the perspective of professionals in both sectors. To this end, exploratory research is proposed, through a methodological triangulation. Specifically, open interviews are conducted with 6 managerial professionals linked to these media, which are completed with a survey of 50 professionals from the radio company and a content analysis of the advertising rates in force in 2023 of the 31 generalist and thematic stations included in the General Media Study. The research shows that, at a formal level, despite the obstacles experienced in terms of the commercialization of the technique, radio is a valid medium for branded content and that the prestige provided by certain stations, their audience and expertise, in terms of the production of journalistic products, provide added value to the brand. However, considering the tactical nature of the medium, depending on the objectives and results pursued by the brand, podcasting may be the most appropriate spoken sound medium.